Maximising Your Immune System and Preventing Infections - Gleeson, M. (Cycle coaching, 2001)
Athletes engaged in heavy training programmes, particularly those involved in endurance events, appear to be more vulnerable than normal to infection. Sore throats and flu-like symptoms are more common in a thletes than in the general population. There is some evidence that this increased susceptibility to infection is due to a depression of immune system function in these individuals. There are two main factors that contribute to making an athlete infected: one is the actual exposure to pathogens, foreign microbes, bacteria and the like that can cause disease effects in the body; the other is the impact of different forms of stress on immune function, the immune system being principally the white blood cells and the lymphoid tissues of the body that help to protect the body against these potentially invading micro-organisms that then produce infections. In general it's now recognised that various forms of stress can result in impaired immune function. These can include the physiological stress of heavy exercise, psychological stress (worry and anxiety), exercising in an extreme environment (heat, cold, altitude) and inadequate diet, particularly inadequate intake of either carbohydrate, protein or micro-nutrients.